PERBAIKAN PERTUMBUHAN DAN HASIL KEDELAI HITAM (Glycine max (L.) MERRIL) DENGAN BIOCHAR DAN PUPUK NPK DI LAHAN KERING - Gerardus Jova; W Widowati; M Marwoto (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The increase in black soybean production is constrained by the decreasing productive land area due to increasing population pressure. Dryland is an alternative that can be developed because of its availability. This study aimed to determine the best dosage of biochar and NPK for black soybean plants in dryland. The treatments were arranged in a randomized block design with two factors that were repeated three times. The first factor was the dose of tobacco Jengkok biochar (0, 10, 15, and 20 t ha-1) and the second factor was the dose of NPK Phonska fertilizer (0, 25, 50, and 100 kg ha-1). Soil used for this study was collected from dry land in Gading Kulon Village, Dau District, Malang Regency. Ten kilograms of the collected soil was placed in a polybag and mixed with biochar according to the treatment dose. After 7 days of biochar application, soybean seeds of Detam 1 variety were planted, and soil samples were taken to observe soil organic C, N, P, and K contents. NPK fertilizer was applied according to the treatment dose at 10 days after planting, Plant height and number of leaves were observed at 2, 4, and 6 weeks after planting. Biomass and crop yields were observed at physiological maturity at 85 days after planting. The results showed that the highest levels of organic C, total N, and K were at a dose of 20 t biochar ha-1, but the use of 15 t biochar ha-1 was the optimum dose for biomass and yield of black soybeans. The highest seed weight was obtained from 100 kg NPK ha-1.